Study of the Effect of Electron Irradiation on the Morphology and Conductive Properties of Silicon Oxide - Kadyrzhanov, K.K. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Study of the Effect of Electron Irradiation on the Morphology and Conductive Properties of Silicon Oxide